(untitled) (Eurasian Research Bulletin, 2022)
Coronavirus infection (COVID-19), an acute infectious disease caused by the SARS-CoV-2 virus, is characterized by activation of the hemostasis system, which in the most severe cases can lead to the development of consumption coagulopathy. Coronavirus disease 2019 (COVID-19) in severe cases leads to a cytokine storm, a systemic inflammatory response, and coagulopathy, which is one of the worst prognostic factors. Coagulopathy in COVID-19 is accompanied by a pronounced increase in the level of D-dimer and fibrin/fibrinogen breakdown products, while the deviation of other indicators (prothrombin time, activated partial thromboplastin time, platelet count) at the onset of the disease is relatively rare. This article will consider the role and intensive care of coagulopathy against the background of coronavirus infection.